Corporate Governance Index and Financial Performance: Mediated by the Risk Management Committee - Suparman, Meiliana; Ng, Judson (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2024)
The influence of election politics on management risk in companies as well as the influence of politics on financial performance. This research aims to analyze the influence of the corporate governance index on financial performance mediated by the risk management committee (RMC), especially in the consumer goods industry which is a priority for consumers. This research used a quantitative and purposive sampling technique where the sample is 85 listed consumer goods companies on the Indonesian stock exchange from 2018-2022. The data analysis method in this research is multiple regression. The conclusion that can be drawn is that corporate governance can influence financial performance depending on several measurements. The results of this test provide a significant relationship between corporate governance and financial performance measurement by ROE, Tobin’s Q, EVA and TSR ratios mediated by the risk management committee.